2011
DOI: 10.1063/1.3593269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of O2+, H2++ O2+, and N2++ O2+ ion-beam irradiation on the field emission properties of carbon nanotubes

Abstract: The effect of O2+, H2++ O2+, and N2++ O2+ ion-beam irradiation of carbon nanotubes (CNTs) films on the chemical and electronic properties of the material is reported. The CNTs were grown by the chemical vapor deposition technique (CVD) on silicon TiN coated substrates previously decorated with Ni particles. The Ni decoration and TiN coating were successively deposited by ion-beam assisted deposition (IBAD) and afterwards the nanotubes were grown. The whole deposition procedure was performed in situ as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additionally, the multi-step nature of the post-treatment procedure contributes to the elevated production costs of N-CNTs. To address these challenges, ion and plasma treatment methods are promising, offering precise control over nitrogen doping parameters [39][40][41][42][43][44][45]. Studies have demonstrated that plasma treatment, influenced by parameters like plasma power, pressure, and exposure time, can lead to N-CNTs with varying nitrogen content (up to 8-20 at.%) embedded into their wall structure [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the multi-step nature of the post-treatment procedure contributes to the elevated production costs of N-CNTs. To address these challenges, ion and plasma treatment methods are promising, offering precise control over nitrogen doping parameters [39][40][41][42][43][44][45]. Studies have demonstrated that plasma treatment, influenced by parameters like plasma power, pressure, and exposure time, can lead to N-CNTs with varying nitrogen content (up to 8-20 at.%) embedded into their wall structure [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of this defect formation is well understood by a parameter known as the displacement per atom (dpa) which is a very useful tool for understanding the extent of surface modification of a carbon nanotube via ion irradiation. This ion irradiation technique is particularly significant as here the defects are created in a controlled fashion [8,9]. Ion irradiation leads to some defects in MWCNT, alters the CNT composition due to ion incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach adopted in the present contribution, involves the use of titanium oxynitride (TiN x O y ) thin films which, additionally, presents low residual stress, good thermal-electrical conductivity, and is compatible with the fabrication of devices. 12 Regarding the strain, it is well-known that ions arriving at the substrate with enough energy (>100 eV) are implanted giving rise to stress. [13][14][15][16][17] A typical example involves xenon atoms that, because of their large sizes, occupy smaller places inside the silicon lattice inducing stress in the network outwards and parallel to the silicon surface by the knock-on process.…”
Section: Introductionmentioning
confidence: 99%